Governance Partnership Facility Final Report 2009-2015 : Results, Lessons, and Legacy - Governance Partnership Facility (World Bank, Washington, DC, 2016)
Over the past five years, the World Bank has made significant progress supporting governance as a core element in operations to end extreme poverty and boost shared prosperity. To help its clients, the Bank strives to deepen its understanding of the environment through the design and implementation of its projects. Since the inception of the Governance and Anticorruption (GAC) Strategy in 2008, the Governance Partnership Facility (GPF) has played a vital role in the success of its implementation.